Faktor-Faktor Yang Memengaruhi Income Smoothing Dengan Mediasi Effective Tax Rates - Nathania Clarissa; Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to obtain empirical evidence about the effect of profitability, leverage and institutional ownership on income smoothing with effective tax rates as mediating variable. The sample used in this research is 35 property, real estate and building construction companies from a total population of 56 companies listed consistently on Indonesia Stock Exchange in 2017-2019. The side technique used is purposive sampling and the valid data was 35 companies. This study uses Structural Equation Model (SEM) which was helped by Smart PLS 3.0. The results showed that institutional ownership has a positive effect on income smoothing, leverage has a positive effect on effective tax rates, profitability has a negative effect on effective tax rates, while profitability, leverage and effective tax rates has no effect on income smoothing. Also, effective tax rates have no effect on mediate profitability and leverage through income smoothing. The implication of this research is the need to increase cautiousness of stakeholders in reading financial reports due to the possibility of income smoothing which could lead into inaccurate decisions.